Police video picketing action during lettuce thinning - Manuel Echavarria::::::photographer:::
Police video picketing action during lettuce thinning. Echavarria recalls how Roy Miname, son of grower Yataro Minami, gave him a karate chop to the neck after he had walked onto one of his fields to get workers to walk off their jobs. Echavarria said the Minamis filed trespassing charges against him, and made the charges stick. The incident was one of many in which UAW members committed civil disobedience to challenge laws that denied them access to the work place, a right long enjoyed by other industrial workers.